Fleksibel Holder Kamera Otomatis Berbasis Autocentering Kamera Berdasarkan Posisi Wajah - Salman Farizy Nur; Dahnial Syauqy; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The phenomenon that happens a lot among us everyday about the number of self-documenting behavior at all times is very close to our lives. With a variety of reasons to just want to document yourself as a marker of memorable activities or just want to publish it on social media. Just like the terms selfie and wefie are very familiar to our ears. However, there are still problems with taking pictures taken manually. Both in terms of the cellphone itself that does not have a front camera so the user cannot determine the correct position. Or the reach of the user's hand that is not enough to get the ideal photo position. Based on these problems, research is used to at least automate activities carried out manually. So that it can help users to be more comforTabel and effective. In this study using two microprocessors namely raspberry pi as a container for coding functions and Arduino Uno as a servo motor drive. This holder moves 90 degrees to the left and 90 degrees to the right. the function of this camera holder is to position the face right in the middle of the frme with an 80% success rate.